Curcumin alleviates 1-methyl- 4-phenyl- 1,2,3,6-tetrahydropyridine- induced Parkinson’s disease in mice via modulating gut microbiota and short-chain fatty acids - Cai, Benchi; Zhong, Lifan; Wang, Qitong; Xu, Wendi; Li, Xi; Chen, Tao (Frontiers in Pharmacology, 2023)
Background: Microbiota-gut-brain axis has been proposed as a potential therapeutic target of PD. The effects of curcumin against Parkinson have been demonstrated, but its neuroprotective mechanisms remain unknown. Our study investigated the potential mechanisms by which curcumin ameliorate Parkinson’s disease by microbiota-gut-brain axis. Methods: The mice were randomly divided into four groups, including control, Curcumin, MPTP, and MPTP+Curcumin groups. Behavioral test、Intestinal motility test and Fecal parameter measurement assess motor deficits and gastrointestinal dysfunction. Western Blot and immunofluorescence measured the loss of dopaminergic neurons and intestinal barrier function. Shotgun metagenomic sequencing and LC-MS were parallelly performed on mice fecal to investigate alterations in microbiota and metabolites. Results: We found that Curcumin alleviated motor deficits and the loss of dopaminergic neurons in MPTP-induced mice. Curcumin ameliorated gastrointestinal dysfunction and intestinal barrier dysfunction in MPTP-induced mice. Curcumin reduced gut microbial dysbiosis and modulated carbohydrate metabolism in MPTP-induced mice. Curcumin restored short-chain fatty acid (SCFA) profiles in MPTP-induced mice. Conclusion: Taken together, these results indicated that curcumin against Parkinson’s disease by regulating the gut microbiota and short-chain fatty acids